Electro-adsorption material for electrochemically extracting bromine as well as preparation method and application of electro-adsorption material

Through the electrochemical extraction technology of bismuth bromine oxide nanosheets and PEDOT composite materials, the problem of poor adsorption capacity and circulation performance of bromine element extraction in oil field brine is solved, and an efficient and environmentally friendly bromine element extraction effect is achieved.

CN119285048AActive Publication Date: 2025-01-10XINJIANG UNIVERSITY

Patent Information

Application Number
CN202411467416.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-10
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

When extracting bromine elements in oil field brine, the existing electrochemical ion exchange method has low adsorption capacity and poor circulation performance, which cannot effectively meet the actual application needs, and the process is complex, high cost and not environmentally friendly.

Method used

The composite material of bismuth bromine oxide nanosheets and polyethylenedioxythiophene (PEDOT) is used as the electro-adsorption material, and PEDOT is synthesized and coated on the surface of bismuth bromine oxide nanosheets by hydrothermal method to form a composite with high specific surface area and conductivity. Material, used for electrochemical extraction of bromine.

Benefits of technology

It improves the adsorption capacity, adsorption rate and selectivity of bromine elements, and has good cycle stability and low dissolution. It is suitable for the extraction of bromine elements in oilfield brine. It has a simple process, high efficiency, low cost and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285048A_ABST
    Figure CN119285048A_ABST
Patent Text Reader

Abstract

The invention provides an electro-adsorption material for electrochemically extracting bromine as well as a preparation method and application of the electro-adsorption material. The electro-adsorption material comprises bismuth oxybromide nanosheets and poly (3, 4-ethylenedioxythiophene) loaded on the surfaces of the bismuth oxybromide nanosheets, and the mass ratio of the bismuth oxybromide nanosheets to the poly (3, 4-ethylenedioxythiophene) is (1-10): (0.1-5). The electro-adsorption material provided by the invention has relatively large adsorption capacity, good cycle stability and excellent selective adsorbability, still has adsorption capacity for a solution with the bromine ion content lower than 100mg / L, and is suitable for being applied to extraction of bromine from oilfield brine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bromine extraction, and in particular relates to an electric adsorption material for electrochemical extraction of bromine, a preparation method and application thereof. Background Art

[0002] Bromine is one of the important chemical raw materials, mainly used in fine chemicals, high-end manufacturing, environmental protection, petrochemicals, medicine, energy storage and other fields. It has more than 100 related high value-added products and is a necessary resource for a complete industrial system. The demand for bromine and bromine-based chemicals has been increasing year by year, and they are in short supply in my country. Bromine resource types mainly include groundwater from oil and gas fields, brine from salt lakes, bitter brine from sea salt fields and brine from salt mines. Among them, underground brine from oil and gas fields and brine from salt lakes are brine bromine resources with the highest bromine concentration and the best quality. Therefore, the extraction of bromine from brine has received more and more attention.

[0003] my country's bromine resources are of low grade and small in total, mainly from underground brine in Shandong Province. Due to continuous mining year after year, the bromine content of underground brine has dropped rapidly, which has increased the cost and difficulty of bromine extraction. Therefore, the development of bromine extraction technology suitable for low-grade resources has received increasing attention. In addition, due to process technology and other issues, the utilization rate of underground brine is low, resulting in a large waste of resources. Bromine resources are facing a crisis, and more bromine-containing resources need to be developed and utilized. However, there are many challenges in extracting bromine from brine, such as the low content of bromine in brine and the chlorine in brine interfering with the extraction of bromine.

[0004] In order to selectively extract bromine from brine, a variety of bromine extraction technologies have emerged, including the more common ones such as adsorption, solvent extraction, precipitation, etc. Taking environmental friendliness into consideration, ion exchange, membrane separation and electrochemical ion exchange (ESIX) have been proposed. Compared with ESIX technology, other technologies have disadvantages such as long production cycle, high cost, environmental pollution and complex process. Therefore, the more efficient, energy-saving and environmentally friendly ESIX technology has attracted much attention. This technology selectively achieves the target ions (such as Li) by adjusting the redox state of the electroactive ion exchange materials (EXIMs) coated on the thin film electrodes. + Br - , Cl - ,I - , Cs + With the continuous improvement and optimization of electroactive ion exchange materials, the adsorption capacity of target ions and the cyclic stability of the materials themselves have been significantly improved.

[0005] The ESIX technology has mild application conditions and uses electricity as the driving force. In addition to the chemical or physical adsorption of the membrane material itself, the application of potential will increase its adsorption and desorption of anions and cations, which can be used to separate ions with lower concentrations in the solution; no chemical regeneration is required during the separation process, avoiding secondary pollution caused by chemical regeneration agents. The key to applying this technology to the separation of bromine from oilfield brine is to study a functional membrane material that is both electroactive and selective for adsorption of bromide ions. Electroactive materials can conduct both electrons and ions, and the target ions can be inserted and removed by changing the redox state of the electroactive materials. However, the electrode active materials currently used for the extraction of bromine from oilfield brine have low adsorption capacity and poor cycle performance, which cannot effectively meet the actual application needs of bromine extraction from oilfield brine. Summary of the invention

[0006] In order to solve all or part of the above technical problems, the present invention provides the following technical solutions: One of the purposes of the present invention is to provide an electrosorption material for electrochemical extraction of bromine, the electrosorption material comprising bismuth oxybromide nanosheets and polyethylene dioxythiophene (PEDOT) coated on the surface of the bismuth oxybromide nanosheets, the mass ratio of the bismuth oxybromide nanosheets to the polyethylene dioxythiophene being 1-10:0.1-5.

[0007] The PEDOT in the electro-adsorption material forms a molecular chain with a conjugated structure. There are freely movable π electrons on the molecular chain. When an electric field is applied, the π electrons move in a direction to form an electric current. Compounding it with bismuth oxybromide nanosheets can improve the conductivity and adsorption performance of the composite material. The electro-adsorption material has a large adsorption capacity, a fast adsorption rate and excellent selective adsorption for bromine, and is not interfered by other anions in the sample during adsorption; and the composite material also exhibits good cycle stability and low dissolution loss.

[0008] In some embodiments, according to the BET test, the specific surface area of ​​the electrosorption material is 5 to 10 times that of a simple bismuth oxybromide nanosheet. The surface of a simple bismuth oxybromide nanosheet is relatively smooth. When a simple bismuth oxybromide nanosheet is directly used as a bromine adsorption material, the conductivity is poor and the adsorption efficiency is low. The present invention finds that the surface roughness of the bismuth oxybromide nanosheet coated with PEDOT increases, and the rough surface increases the specific surface area of ​​the material, making its specific surface area more than 5 to 10 times that of a single bismuth oxybromide nanosheet without compounding, providing more abundant active sites for the capture and release of bromine.

[0009] In some embodiments, the bismuth oxybromide nanosheet has a diameter of 50-1000 nm and a thickness of 50-500 nm, and the coating thickness of the polyethylenedioxythiophene on the surface of the bismuth oxybromide nanosheet is 10-1000 nm.

[0010] According to the thermogravimetric analysis test (TG test), the initial weight loss temperature of the electrosorption material is 350°C, which indicates that it has good high temperature resistance and can adapt to most brine temperature environments.

[0011] The second object of the present invention is to provide a method for preparing the electrosorption material, comprising: Bismuth oxybromide nanosheets were synthesized by hydrothermal method; A mixed reaction system containing the bismuth oxybromide nanosheet, 3,4-ethylenedioxythiophene (EDOT), ammonium persulfate and / or ferric chloride is reacted at 0°C to 5°C, so that the 3,4-ethylenedioxythiophene is polymerized to form polyethylenedioxythiophene and coated on the surface of the bismuth oxybromide nanosheet, thereby obtaining an electrosorption material composited with bismuth oxybromide nanosheet and polyethylenedioxythiophene.

[0012] In the presence of ammonium persulfate and / or ferric chloride, EDOT undergoes a polymerization reaction to generate PEDOT and is coated on the surface of bismuth oxybromide nanosheets. The surface roughness of the electrosorption material prepared in this way is significantly improved, and the coating thickness is appropriate, which enables bromide ions to pass through the PEDOT shell and enter the BiOBr interlayer.

[0013] In some embodiments, the concentration of bismuth oxybromide nanosheets in the mixed reaction system is 23-200 g / L.

[0014] In some embodiments, the mass ratio of bismuth oxybromide nanosheets to 3,4-ethylenedioxythiophene in the mixed reaction system is 1-10:0.1-5.

[0015] In some embodiments, the concentration of ammonium persulfate and / or ferric chloride in the mixed reaction system is 0.1-5 mol / L.

[0016] In some embodiments, the reaction time is 8 to 16 hours.

[0017] In some embodiments, the hydrothermal method includes: reacting a reaction system containing a bismuth source, a bromine source, a strong base and a solvent at a temperature of 150-180° C., wherein the pH value of the reaction system is 5-8, to obtain bismuth oxybromide nanosheets.

[0018] In some embodiments, the concentration of the bismuth source in the reaction system is 0.1-1 mol / L, and the concentration of the bromine source is 0.1-1 mol / L.

[0019] In some embodiments, the bismuth source includes Bi(NO3)3∙5H2O, and the bromine source includes KBr.

[0020] In some embodiments, the concentration of the strong base in the reaction system is 0.1 mol / L. The strong base includes, for example, NaOH, KOH, or a combination of more than one thereof.

[0021] In some embodiments, the reaction time is 8 to 12 h.

[0022] A third object of the present invention is to provide a bromine active electrode, wherein the bromine active electrode comprises the electrosorption material.

[0023] In some embodiments, the bromine active electrode comprises a conductive substrate and a composite membrane layer formed on the conductive substrate, wherein the composite membrane layer comprises the electrosorption material, a conductive material and a binder.

[0024] In some embodiments, the mass ratio of the electrosorption material, the conductive material and the binder is 4~8:0.1~1:0.5~1.5. For example, the electrosorption material, the conductive material and the binder are uniformly mixed according to the above mass ratio and a proper amount of solvent is added to form a slurry, and the slurry is coated on a conductive substrate and cured to form the composite film layer. The slurry made of the electrosorption material has good ductility, and a small amount of preparation can be used in a large area for a long time; the electrosorption material has low cost and good economic efficiency, and thus has industrial and commercial prospects.

[0025] In some embodiments, the conductive material includes one or a combination of carbon black, graphene, and acetylene black, but is not limited thereto.

[0026] In some embodiments, the binder includes one or a combination of polyvinylidene fluoride, polyacrylic acid, polymethacrylic acid, and polyvinyl alcohol, but is not limited thereto.

[0027] In some embodiments, the conductive substrate is made of one or more of carbon, titanium, and nickel, but is not limited thereto. For example, the conductive substrate is carbon paper, a carbon sheet, a titanium sheet, or nickel foam.

[0028] A fourth object of the present invention is to provide a system for extracting bromine, comprising: a working electrode, a counter electrode and a reference electrode, wherein the working electrode is the bromine active electrode.

[0029] A fifth object of the present invention is to provide the use of the electro-adsorption material, the bromine-active electrode or the bromine extraction system in extracting bromine from brine.

[0030] In some embodiments, the brine is oilfield brine. The present invention finds that the electrosorption material composed of bismuth oxybromide nanosheets and polyethylene dioxythiophene has strong stability, and the extraction of bromide ions is controlled by the applied redox potential and is not easily interfered by other impurities in the sample, and is particularly suitable for the extraction of bromide ions in oilfield brine or other more extreme environments.

[0031] A sixth object of the present invention is to provide a method for extracting bromine from oilfield brine, wherein the system for extracting bromine comprises: Pre-treating the bromine active electrode in the system, the pre-treating comprising: placing the bromine active electrode in water and applying a voltage of -0.8 to -1.2 V to desorb at least part of the bromine in the bromine active electrode; The pretreated bromine active electrode is placed in oilfield brine, and a voltage of 0.6-1.2V is applied to enable the bromine active electrode to adsorb bromide ions in the oilfield brine to achieve bromine extraction.

[0032] The method for extracting bromine from oilfield brine does not require acid or alkali elution of bromide ions, and the adsorption and desorption of bromine can be achieved after applying voltage. The overall process of the entire electrical adsorption process is simple, efficient, low-cost, and environmentally friendly.

[0033] Compared with the prior art, the present invention has at least the following beneficial effects: the electrosorption material for extracting bromine prepared by the present invention has a large adsorption capacity, good cycle stability and excellent selective adsorption; the electrosorption material still has a certain adsorption capacity for solutions with a bromide ion content of less than 100 mg / L. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0035] Figure 1 is an electron microscope image of the BiOBr nanosheet prepared in one embodiment of the present invention; Figure 2 is an electron microscope image of the BiOBr@PEDOT composite material prepared in one embodiment of the present invention; Figure 3 Schematic diagram of the three-electrode system constructed in one embodiment of the present invention for extracting bromide ions.

[0036] Figure 4It is a comparison diagram of the adsorption performance of the bromine active electrode prepared in one embodiment of the present invention under voltage conditions of 0.6V, 0.8V, 1.0V, and 1.2V respectively; Figure 5 It is the change of adsorption capacity of the bromine active electrode prepared by one embodiment of the present invention for a solution with an initial bromine concentration of 150 mg / L when the bromine active electrode is not replaced (green mark) and each time the bromine active electrode is replaced (orange mark). DETAILED DESCRIPTION

[0037] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention. The specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and for teaching those skilled in the art. Unless otherwise specified, The raw materials and reagents used in the following specific embodiments are all commercially available, and the detection and characterization methods used are conventional methods in the art.

[0038] Example 1 3.88g of and 0.952 g of KBr were dispersed in 120 mL of ultrapure water and stirred continuously, and then 1 M NaOH was added to the mixture to adjust the pH value to 6; after magnetic stirring for 0.5 h, the mixture was poured into a 150 mL polytetrafluoroethylene-lined stainless steel autoclave and heated in a constant temperature drying oven at 160 ° C for 24 h to obtain BiOBr; after the reaction was completed, it was cooled at room temperature, and then the prepared BiOBr was repeatedly rinsed with ultrapure water and ethanol to eliminate residual ions, and the washed BiOBr was dried in a vacuum oven at 60 ° C for 12 h; 4.58 g of 3,4-ethylenedioxythiophene was dropped into 100 ml of deionized water and stirred to form a solution A. 3.05 g of the prepared bismuth oxybromide nanosheets was added to the solution A and stirred for 1 hour to form a solution B. 3.43 g of ammonium persulfate was dissolved in 30 ml of deionized water to form an ammonium persulfate solution. The ammonium persulfate solution was added to the stirring solution B to obtain a solution C. The solution C was stirred at 0°C for 12 hours to obtain a BiOBr@PEDOT composite material. 100 ml of 0.001 mol / L HCl solution and deionized water were used to repeatedly rinse the composite material three times to remove residual polymers and other ions. The washed composite material was dried in a vacuum drying oven at 50°C for 12 hours.

[0039] Figure 1 is an electron microscope image of BiOBr prepared in this example. Figure 1It can be seen that BiOBr presents a stacked nanosheet structure with a sheet diameter of approximately 787 nm and a sheet thickness of approximately 81 nm. Figure 2 is an electron microscope image of the BiOBr@PEDOT composite material prepared in this example, compared with Figure 1 , 2 It can be seen that the BiOBr in the composite material still maintains its original nanosheet structure, indicating that the modification of PEDOT has not changed the structure of BiOBr. In addition, PEDOT is well coated on the surface of BiOBr nanosheets, turning the original smooth surface of BiOBr nanosheets into a relatively rough surface, which increases the specific surface area of ​​the composite material by 6 times compared with that of pure BiOBr nanosheets, providing more abundant active sites for the capture and release of Br.

[0040] According to TG characterization, the mass ratio of BiOBr to PEDOT in the BiOBr@PEDOT composite material was tested to be approximately 1:1.5.

[0041] According to thermogravimetric analysis, the initial weight loss temperature of the BiOBr@PEDOT composite material is 350°C, indicating that it has good high temperature resistance.

[0042] The bromine active electrode was prepared by using the BiOBr@PEDOT composite material prepared above: dry BiOBr@PEDOT composite material powder, polyvinylidene fluoride and carbon black were mixed in a mass ratio of 8:1:1, and N-methylpyrrolidone twice the volume of the solid powder was added, and the mixture was ground for 2 h to form a uniform slurry; then the slurry was applied on a 3 cm 2 The coating thickness is 0.5 mm on the carbon paper and dried at 80°C for 5 h to form a composite film layer on the carbon paper to obtain a bromine active electrode.

[0043] An electrochemical workstation was used to perform adsorption-desorption operations in a three-electrode system, with the bromine-active electrode prepared as above as the working electrode, the platinum wire as the counter electrode, and the Ag / AgCl electrode as the reference electrode; before adsorption, the working electrode was pretreated, the working electrode was placed in pure water, and a potential of -1V was applied to desorb the bromide ions in the working electrode; the working electrode pretreated as above was placed in a bromine-containing solution with a concentration of 100 mg / L, and adsorption tests were performed under voltage conditions of 0.6V, 0.8V, 1.0V, and 1.2V. Figure 3 This is a schematic diagram of the constructed three-electrode system for extracting bromide ions.

[0044] Figure 4 is the adsorption performance of the bromine active electrode of this embodiment under different voltage conditions, from Figure 4It can be seen that the bromine active electrode has the ability to adsorb bromide ions in the voltage range of 0.6~1.2V, and the adsorption performance is better at 1.0V, and the adsorption capacity can reach 16.41mg / g. The bromine active electrode has a high adsorption rate (the adsorption data shown in Table 1 refers to the time required to reach the maximum adsorption amount), and the maximum adsorption amount can be reached at 30min. Compared with conventional adsorbents that take about two hours to reach adsorption equilibrium, the adsorption rate is significantly improved.

[0045] Table 1 Bromine adsorption performance of the bromine active electrode in Example 1 under different voltage conditions ; The bromine active electrode prepared in Example 1 was used to test its adsorption performance under the condition of a voltage of 1.0 V when the bromide ion content in the solution was low. Figure 5 The adsorption capacity of the bromine active electrode prepared in Example 1 for a solution with an initial bromine concentration of 150 mg / L is shown without replacing the bromine active electrode (green mark) and each time the bromine active electrode is replaced (orange mark). It can be seen that when the bromine active electrode is replaced, the adsorption capacity of the first three times is higher, because the bromine concentration in the solution is above 100 mg / L at this time; after three adsorptions, the bromine concentration in the solution decreases below 100 mg / L, but the adsorption capacity of the next five times remains stable, and the adsorption capacity of each of the last five times remains above 10 mg / g. Without replacing the membrane electrode. When the same electrode is used repeatedly and the solution concentration continues to decrease, the bromine active electrode prepared by the present invention still has a certain adsorption capacity in subsequent use.

[0046] Example 2 3.88g of and 0.952 g of KBr were dispersed in 120 mL of ultrapure water and stirred continuously, and then 1 M NaOH was added to the mixture to adjust the pH value to 6; after magnetic stirring for 0.5 h, the mixture was poured into a 150 mL polytetrafluoroethylene-lined stainless steel autoclave and heated in a constant temperature drying oven at 160 ° C for 24 h to obtain BiOBr; after the reaction was completed, it was cooled at room temperature, and then the prepared BiOBr was repeatedly rinsed with ultrapure water and ethanol to eliminate residual ions, and the washed BiOBr was dried in a vacuum oven at 60 ° C for 12 h; 15.25 g of 3,4-ethylenedioxythiophene was dropped into 100 ml of deionized water and stirred to form a solution A. 3.05 g of the prepared bismuth oxybromide nanosheets were added to the solution A and stirred for 1 hour to form a solution B. 8.1 g of ferric chloride was dissolved in 30 ml of deionized water to form a ferric chloride solution. The ferric chloride solution was added to the stirring solution B to obtain a solution C. The solution C was stirred at 5°C for 16 hours to obtain a BiOBr@PEDOT composite material. 100 ml of 0.001 mol / L HCl solution and deionized water were used to repeatedly rinse the composite material three times to remove residual polymers and other ions. The washed composite material was dried in a vacuum drying oven at 50°C for 12 hours.

[0047] The bromine active electrode prepared in Example 2 was tested by the same method as in Example 1. The adsorption capacity, adsorption rate and cycle stability of the bromine active electrode prepared in this embodiment were comparable to those in Example 1.

[0048] Example 3 3.88g of and 0.952 g of KBr were dispersed in 120 mL of ultrapure water and stirred continuously, and then 1 M NaOH was added to the mixture to adjust the pH value to 6; after magnetic stirring for 0.5 h, the mixture was poured into a 150 mL polytetrafluoroethylene-lined stainless steel autoclave and heated in a constant temperature drying oven at 160 ° C for 24 h to obtain BiOBr; after the reaction was completed, it was cooled at room temperature, and then the prepared BiOBr was repeatedly rinsed with ultrapure water and ethanol to eliminate residual ions, and the washed BiOBr was dried in a vacuum oven at 60 ° C for 12 h; 0.305 g of 3,4-ethylenedioxythiophene was dropped into 100 ml of deionized water and stirred to form a solution A. 3.05 g of the prepared bismuth oxybromide nanosheets were added to the solution A and stirred for 1 hour to form a solution B. 6.85 g of ammonium persulfate was dissolved in 30 ml of deionized water to form an ammonium persulfate solution. The ferric chloride solution was added to the stirring solution B to obtain a solution C. The solution C was stirred at 3°C ​​for 8 hours to obtain a BiOBr@PEDOT composite material. 100 ml of 0.001 mol / L HCl solution and deionized water were used to repeatedly rinse the composite material three times to remove residual polymers and other ions. The washed composite material was dried in a vacuum drying oven at 50°C for 12 hours.

[0049] The bromine active electrode prepared in Example 3 was tested by the same method as in Example 1. The adsorption capacity, adsorption rate and cycle stability of the bromine active electrode prepared in this embodiment were comparable to those in Example 1.

[0050] Comparative Example 1 In Comparative Example 1, a bromine active electrode was constructed using pure BiOBr nanosheets. The BiOBr nanosheets were the BiOBr nanosheets prepared in Example 1, and the rest of the steps were the same as in Example 1.

[0051] By comparing Example 1 and Comparative Example 1, it is found that compared with the bromine active electrode constructed with simple BiOBr nanosheets, the bromine active electrode based on the BiOBr@PEDOT composite material exhibits better conductivity and adsorption capacity. Under the same adsorption conditions, when the desorption liquid is deionized water, the adsorption capacity of the bromine active electrode of Example 1 is increased by 10 times compared with that of Comparative Example 1, and the adsorption rate is increased by 50%.

[0052] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, pure PEDOT material is mixed with polyvinylidene fluoride and carbon black in a mass ratio of 8:1:1 to prepare an electrode.

[0053] The present invention uses the bromine active electrode in the above-mentioned embodiment 1, comparative example 1, and comparative example 2 to test the real oilfield brine sample (Br - The bromine extraction test was performed in a bromine-free electrode (with a concentration of about 200 mg / L). When a potential of 1.0 V was applied and other conditions were the same, the adsorption capacity of pure BiOBr in Comparative Example 1 was 4.7 mg / g, the adsorption capacity of pure PEDOT material in Comparative Example 2 was 6.8 mg / g, and the adsorption capacity of the bromine active electrode in Example 1 was 35 mg / g, indicating that a certain synergistic effect was produced after BiOBr and PEDOT were combined. The adsorption capacity of pure BiOBr is much smaller than that of BiOBr@PEDOT composite materials. This is because the conductivity of pure BiOBr electrodes is poor, while the doping of PEDOT can improve the conductivity of bromine active electrodes, and can also increase the surface roughness of BiOBr nanosheets, providing abundant active sites.

[0054] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0055] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0056] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another element.

Claims

1. An electrosorption material for electrochemical extraction of bromine, characterized in that: include: Bismuth oxybromide nanosheets and polyethylene dioxythiophene coated on the surface of the bismuth oxybromide nanosheets, wherein the mass ratio of the bismuth oxybromide nanosheets to the polyethylene dioxythiophene is 1-10:0.1-5.

2. The electrosorption material according to claim 1, characterized in that: According to the BET test, the specific surface area of ​​the electrosorption material is 5 to 10 times that of the bismuth oxybromide nanosheets; And / or, the bismuth oxybromide nanosheet has a sheet diameter of 50 to 1000 nm and a thickness of 50 to 500 nm, and the polyethylene dioxythiophene coating thickness on the surface of the bismuth oxybromide nanosheet is 10 to 1000 nm; And / or, according to thermogravimetric analysis, the initial weight loss temperature of the electrosorption material is 350°C.

3. The method for preparing the electrosorption material according to claim 1 or 2, characterized in that: include: Bismuth oxybromide nanosheets were synthesized by hydrothermal method; A mixed reaction system containing the bismuth oxybromide nanosheet, 3,4-ethylenedioxythiophene, ammonium persulfate and / or ferric chloride is reacted at 0-5° C. to polymerize the 3,4-ethylenedioxythiophene to form polyethylenedioxythiophene and coat the surface of the bismuth oxybromide nanosheet, thereby obtaining an electrosorption material composited with bismuth oxybromide nanosheet and polyethylenedioxythiophene.

4. The preparation method according to claim 3, characterized in that: The concentration of bismuth oxybromide nanosheets in the mixed reaction system is 23-200 g / L; And / or, the mass ratio of bismuth oxybromide nanosheets to 3,4-ethylenedioxythiophene in the mixed reaction system is 1-10:0.1-5; and / or, the concentration of ammonium persulfate and / or ferric chloride in the mixed reaction system is 0.1-5 mol / L; And / or, the reaction time is 8 to 16 h.

5. A bromine-active electrode, characterized in that: Comprising the electrosorption material according to claim 1 or 2.

6. The bromine active electrode according to claim 5, characterized in that: The bromine active electrode comprises a conductive substrate and a composite membrane layer formed on the conductive substrate, wherein the composite membrane layer comprises the electric adsorption material according to claim 1 or 2, a conductive material and a binder.

7. The bromine-active electrode according to claim 6, characterized in that: The mass ratio of the electric adsorption material, the conductive material and the binder is 4-8:0.1-1:0.5-1.5; And / or, the conductive material includes one or a combination of carbon black, graphene, and acetylene black; And / or, the binder includes one or a combination of polyvinylidene fluoride, polyacrylic acid, polymethacrylic acid, and polyvinyl alcohol; And / or, the material of the conductive substrate includes one or a combination of carbon, titanium, and nickel.

8. A system for extracting bromine, characterized in that: include: A working electrode, a counter electrode and a reference electrode, wherein the working electrode is the bromine active electrode as described in any one of claims 5 to 7.

9. Use of the electric adsorption material according to claim 1 or 2, the bromine active electrode according to any one of claims 5 to 7, or the bromine extraction system according to claim 8 in extracting bromine from brine; Preferably, the brine is oilfield brine.

10. A method for extracting bromine from oilfield brine, characterized in that: The system for extracting bromine according to claim 8 comprises: Pre-treating the bromine active electrode in the system, the pre-treating comprising: placing the bromine active electrode in water and applying a voltage of -0.8 to -1.2 V to desorb at least part of the bromine in the bromine active electrode; The pretreated bromine active electrode is placed in oilfield brine, and a voltage of 0.6-1.2V is applied to enable the bromine active electrode to adsorb bromide ions in the oilfield brine to achieve bromine extraction.

Citation Information

Patent Citations

  • Poly(3,4-ethylenedioxythiophene) aligned array layer thin-film electrode material and preparing method thereof

    CN101587778A

  • Light valve and preparation method thereof

    CN114839760A

  • Preparation method of flexible Bi2Te3 / PEDOT nanowire thermoelectric composite film

    CN117915743A

  • Method of forming charged manganese oxides from discharged active materials

    US20200358092A1

Cited By

  • Iron-doped bismuth oxybromide material, preparation method thereof, membrane electrode and application

    CN122380449A